PENINGKATAN MEDIA PEMBELAJARAN INTERAKTIF PAUD DI KABUPATEN SERANG - Kraugusteeliana, Kraugusteeliana; Saebani, Akhmad (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2022)
The golden age of students where currently early childhood children are very easy to receive various information. At this time, some early childhood education in Baros Village still use conventional learning methods. this is the reason for the need for a paradigm shift that makes learning interesting and interactive. Interactive learning media training is carried out to equip teachers how to make interesting early childhood learning media so that they can quickly find out and understand what the teachers are teaching. The stages carried out The training stages consist of the stages of socialization, training, adjustment of needs, and testing of learning media. Based on the results of the Pretest for 10 questions including the question of country names, state symbols, national anthems and others, the results obtained were around 28 PAUD children answered incorrectly and did not understand the learning material being asked but after using the learning media that had been prepared by the Community Service Team and teachers, the results from the Post test showed significance to 100% with a total of 10 questions for 28 PAUD children with all correct answers